Neural tracking of continuous speech reveals enhanced late responses to degraded speech - Na, Youngmin; Quan, Luong Do Anh; Joo, Hyosung; Choi, Inyong; Woo, Jihwan (Frontiers in Neuroscience, 2026)
IntroductionComprehending degraded speech demands greater cognitive effort. While previous studies have identified the neural pathways involved in processing degraded speech signals, the temporal dynamics of these neural networks remain unclear.MethodsThis study investigated the time course of neural responses to clean and degraded (i.e., noise-vocoded) speech signals using temporal response functions (TRFs).ResultsOur findings reveal that early TRF components (N1TRF and P2TRF) exhibited greater amplitude and temporal precision for clean speech. In contrast, degraded speech elicited additional cortical responses with a longer delay, designated as P400TRF. Subsequent source localization analyses showed that the P400TRF component originates from language processing areas within the temporal and frontal lobes.DiscussionThese findings highlight the role of delayed neural mechanisms in maintaining speech comprehension when intelligibility is compromised, offering novel insights that broaden our understanding of auditory cortical processing under challenging listening conditions.